Isolates ofLactobacillus plantarumandL. reuteridisplay greater antiproliferative and antipathogenic activity than otherLactobacillusisolates. Issue 10 (October 2017) - Bibalan, Meysam Hasannejad; Eshaghi, Morteza; Rohani, Mahdi; Esghaei, Maryam; Darban‐Sarokhalil, Davood; Pourshafie, Mohammad R.; Talebi, Malihe
Abstract : Purpose. : Lactic acid bacteria (LAB) have been associated with many beneficial effects in human digestive physiology. The aim of this study was to evaluate such effect, including attachment, antiproliferation and anti‐pathogenic/antibacterial/antimicrobial properties of LAB isolated from healthy humans. Methodology. : Thirteen isolates, obtained from fecal samples of healthy individuals, were identified by phenotypic and molecular methods. Human colon adenocarcinoma cell line HT‐29 and the cell proliferation kit II (XTT) assay were used for examination of the Lactobacillus adherence and antiproliferative activity, respectively. In addition, the inhibitory effect of Lactobacillus isolates against pathogenic bacteria was examined. Results. : Out of 13 Lactobacillus isolates, 5 (38 %) isolates were non‐adhesive, 4 (31 %) were adhesive and 4 (31 %) were strongly adhesive. Amongst the isolated lactobacilli, L. reuteri showed the highest degree of inhibitory effect against the attachment of the enteropathogens. The XTT assay showed that 3 different isolates had the strongest antiproliferative activity with the maximum effect observed by L. plantarum isolates. Conclusion. : Our results described that different Lactobacillus species isolated from normal fecal samples had different degrees of antiproliferative and anti‐pathogenic/antibacterial/antimicrobial activities. However, no isolates showed all of the examined properties concurrently, suggestive that a combination of Lactobacillus species is needed for an active biological defense system.